BIMBINGAN TEKNIS PELAKSANAAN KEWAJIBAN PERPAJAKAN BENDAHARA DESA DI KECAMATAN KAMPA KABUPATEN KAMPAR - Safitri, Devi; Hariyani, Eka; Supriono (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2025)
This community service activity is one of the requirements for fulfilling higher education's tri dharma. The purpose of this community service activity is to provide training and guidance on how to fulfil the village treasurer's tax obligations, starting from registering to obtain an NPWP, deducting and/or collecting taxes, depositing taxes into the state treasury, submitting tax returns, and providing with holding evidence to the party who is deducted or collected in Kampa District, Kampar Regency. The service team, which consists of academics and students from the Faculty of Economics and Business at the University of Riau, delivers the information via technical advice or training methods, followed by participant evaluations to check their understanding before and after each session. The service activities resulted in a significant increase in participants' comprehension and implementation of their tax duties. This activity project is designed to assist village treasurers in carrying out their tax obligations more effectively, potentially increasing state revenue in the tax sector Keywords: Tax Obligations, Village Treasurer, Village Fund, With holding and Collection of Tax